Rancang Bangun Sistem Pengamanan Data Media Flash Drive dengan Algoritma Rijndael dan Hash SHA-1 - Ichsan, Mochammad; Sam'ani, Sam'ani; Sutami, Sutami; Qamaruzzaman, Muhammad Haris; Haris, Ferdiyani; Suparno, Suparno; Ridzky, Muhammad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
USB Flash Drive is one of the most widely used storage media today, with its small shape, large capacity, and easy to carry anywhere, making USB Flash Drive the most widely used media in data exchange, along with its development, a security system is needed that can protect data stored on USB Flash Drive. The problem of this study is how to create a data security application on USB Flash Drive media? This system aims to provide data protection stored in USB Flash Drive using encryption methods, the system is created using the Delphi XE2 programming language, utilizing two Rijndael cryptographic algorithms and SHA-1 hash. The methods used in writing include data collection methods (Literature Study) and analysis methods, namely system analysis (system weaknesses, system requirements, and system feasibility). This study has succeeded in implementing a data security system for USB Flash Drive media, and testing has been carried out on the results of the implementation. Based on the results of the respondents that have been collected, it produces good response values, thus the system can provide data protection on USB Flash Drive media.